2003
DOI: 10.2466/pr0.92.1.195-200
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Intercultural Communication Apprehension, Ethnocentrism, and Intercultural Willingness to Communicate

Abstract: Communication predispositions influence interactions between individuals from different cultures. Three such predispositions have been found to affect behavior in intercultural contexts: Apprehension about intercultural communication, ethnocentrism, and intercultural willingness to communicate. This study examined differences between men (n = 130) and women (n = 175) on those three predispositions. The analysis showed that men reported experiencing higher apprehension about intercultural communication, being m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…It seems that male students were more risk-taking than females both at the beginning and toward the end of the term, which might be related to the Chinese culture which respects men THEORY AND PRACTICE IN LANGUAGE STUDIES © 2011 ACADEMY PUBLISHER 1220 more (Bond, 1996;Scollon & Scollon, 2000). Meanwhile, they reported to be less sociable than their female counterparts both at the beginning and toward the end of the term, consistent with a number of existing studies (Canada & Pringle, 1995;Lin & Rancer, 2003). Nevertheless, statistically significant difference was observed only in the LCR in both phases (t = 3.99, p = .000; and t = 2.16, p = .03 for phases 1 & 2 respectively), as supported by the independent samples t-test results.…”
Section: A General Pattern Of and Changes In Language Class Risk-taksupporting
confidence: 80%
See 1 more Smart Citation
“…It seems that male students were more risk-taking than females both at the beginning and toward the end of the term, which might be related to the Chinese culture which respects men THEORY AND PRACTICE IN LANGUAGE STUDIES © 2011 ACADEMY PUBLISHER 1220 more (Bond, 1996;Scollon & Scollon, 2000). Meanwhile, they reported to be less sociable than their female counterparts both at the beginning and toward the end of the term, consistent with a number of existing studies (Canada & Pringle, 1995;Lin & Rancer, 2003). Nevertheless, statistically significant difference was observed only in the LCR in both phases (t = 3.99, p = .000; and t = 2.16, p = .03 for phases 1 & 2 respectively), as supported by the independent samples t-test results.…”
Section: A General Pattern Of and Changes In Language Class Risk-taksupporting
confidence: 80%
“…For instance, Krupnick (1985) found that male students interacted more with their instructors than female students. Canada and Pringle (1995) found that female students initiated more faculty-student interactions than male students within mixed-sex classrooms, which was supported by the subsequent research done by Lin and Rancer (2003). Nevertheless, Brady and Eisler"s (1999) study of 24 classes from various disciplines at a major university in America showed that men and women did not differ significantly in terms of their behaviors and interactions with faculty members, and that male-dominated classrooms were rated significantly less interactive than female-dominated and nondominated classrooms.…”
Section: Introductionmentioning
confidence: 71%
“…Moreover, it influenced people's preference for conflict styles in an intercultural encounter (Oommen, 2014), lowered people's satisfaction with the interaction, and inhibited further uncertainty reduction (Neuliep, 2012). Fourth, group differences in ICA have also been found: For example, South Koreans scored higher on ICA than their U.S. counterparts (Merkin, 2009), whereas men tended to have higher ICA than women (Lin & Rancer, 2003b).…”
Section: Intercultural Communication Apprehensionmentioning
confidence: 99%
“…For instance, Gagnon and Bourhis (1996) found that individuals who identified strongly with their in-group were more likely to discriminate against an out-group than those who identified less strongly with their in-group. Some researchers argue that interactants high in ethnocentrism may base their expectations on their own cultural social norms and rules, resulting in misunderstandings of the other interactant's intentions, values, and behavior (Lin and Rancer 2003;Neuliep and McCroskey 1997;Stephan and Stephan 2002). Some researchers argue that interactants high in ethnocentrism may base their expectations on their own cultural social norms and rules, resulting in misunderstandings of the other interactant's intentions, values, and behavior (Lin and Rancer 2003;Neuliep and McCroskey 1997;Stephan and Stephan 2002).…”
Section: Ethnocentrismmentioning
confidence: 99%